2011
DOI: 10.2134/agronj2010.0446
|View full text |Cite
|
Sign up to set email alerts
|

Lemongrass Productivity, Oil Content, and Composition as a Function of Nitrogen, Sulfur, and Harvest Time

Abstract: Lemongrass [Cymbopogon flexuosus (Steud.) Wats, (syn. Andropogon nardus var. flexuosus Hack; A. flexuosus Nees)] is one of the most widely grown essential oil plants in the world. Field experiments were conducted at Verona and Poplarville, MS, to evaluate the effects of N (0, 40, 80, and 160 kg N/ha) and S (0, 30, 60, and 90 kg S/ha) on lemongrass biomass productivity, essential oil content, yield, and oil composition. Overall, the essential oil content varied within 0.35 to 0.6% of the dried biomass. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 29 publications
2
44
0
2
Order By: Relevance
“…Similarly, Zheljazkov et al (2008) showed maximum basil oil yield when the medium rate of nitrogen was applied. Sifola and Barbieri (2006) found that nitrogen fertilization increased above-ground yield, fresh leaf biomass, and oil concentration and yield in basil.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Zheljazkov et al (2008) showed maximum basil oil yield when the medium rate of nitrogen was applied. Sifola and Barbieri (2006) found that nitrogen fertilization increased above-ground yield, fresh leaf biomass, and oil concentration and yield in basil.…”
Section: Discussionmentioning
confidence: 90%
“…Environmental and agrotechnical factors are another group of factors that affect the amount and quality of basil yield. Optimal plant fertilization, in particular nitrogen and potassium fertilization, is of great importance in the cultivation of basil (Kandil et al 2009;Zheljazkov et al 2008;Daneshian et al 2008;Nurzyńska-Wierdak et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Geraniol, linalool, gamma-terpineol, carvacrol, thymol and trans-thujan-4-ol/terpinen-4-ol were the major constituents (Amiri, 2012 (Zheljazkov et al, 2011) due to its major constituents caryophyllene oxide, t-caryophyllene, geranyl acetate, (E)-citral (geranial), (Z)-citral (neral), and trans-geraniol, citronellyl acetate, citronellol, geraniol and limonene.…”
Section: Discussionmentioning
confidence: 99%
“…Cymbopogon flexuosus is a highly productive and vigorous plant that has good yield of dry mass (7-25 t ha -1 ) and higher yield in the production of EO (100 L of EO ha -1 ) (Zheljazkov, Cantrell, Astatkie, & Cannon, 2011) compared to other citral-rich herbs like L. alba (citral chemotype) (~26-67 L of EO ha -1 ) (Zambrano, Buitrago, Durán, Sanchez, & Bonilla, 2013) and A. triphylla (10 L of EO ha -1 ) (Al-Mefleh, Abu Salah, & Abandeh, 2012). These characteristics increase the economic viability for the production of C. flexuosus EO.…”
Section: Introductionmentioning
confidence: 99%